2010
DOI: 10.1007/s13139-010-0031-2
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of TE2A—a Potential Bifunctional Chelator for 64Cu

Abstract: Purpose The development of a new bifunctional chelator, which holds radiometals strongly in living systems, is a prerequisite for the successful application of diseasespecific biomolecules to medical diagnosis and therapy. Recently, TE2A was reported to make kinetically more stable Cu(II) complexes than TETA. Herein, we report a new synthetic route to TE2A and explore its potential as a bifunctional chelator. Methods TE2A was synthesized using the regioselective alkylation of benzyl bromoacetate and successive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“… 32 In a follow-up paper, a new synthesis of the salt-free TE2A was reported that was conjugated to c(RGDyK), but no biodistribution data were reported. 33 Zhang et al . reported a multivalency platform based on the DOTA chelator using c(RGDyK) with no space between the c and (RGDyK) as a model peptide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 In a follow-up paper, a new synthesis of the salt-free TE2A was reported that was conjugated to c(RGDyK), but no biodistribution data were reported. 33 Zhang et al . reported a multivalency platform based on the DOTA chelator using c(RGDyK) with no space between the c and (RGDyK) as a model peptide.…”
Section: Introductionmentioning
confidence: 99%
“…reported a synthesis of TE2A ( 12 ), and the acid decomplexation and reduction potential measurements indicated that Cu‐TE2A is more stable than Cu‐TETA, on the basis of rat biodistribution data showing significantly lower retention of 64 Cu‐TE2A than 64 Cu‐TETA in kidney and liver at 24 h post injection, suggesting a lower extent of demetallation in vivo . In a follow‐up paper, a new synthesis of the salt‐free TE2A was reported that was conjugated to c(RGDyK), but no biodistribution data were reported . Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The approach to GluCAB‐1 Mal for copper complexation was to use a TE2A, a cyclam platform, functionalized with two acetate arms [28–30] . The cyclam was selected as the most appropriate based‐backbone, with a cavity better suited for copper cation able to form highly stable and inert complexes [31,32] .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 For copper complexation, the cyclam backbone was selected as the most appropriate since the cavity is better suited for this cation with highly stable and inert complexes being formed; 28,29 it also appeared to be the most tunable platform considering all the recent successful studies in 64 Cu-PET imaging using cyclam-based chelators. 30,31,32,33,34,35 The approach to Glu-CAB-1 Mal was to use the cyclam platform functionalized with two acetate arms, namely TE2A. Although other cyclam derivatives have proved to be more suitable for the application, TE2A presented the advantage of being a decent copper(II) chelator, 36 while offering two remaining secondary amines that could be functionalized ( Figure 2) for passive and active targeting.…”
Section: Introductionmentioning
confidence: 99%
“…37 Furthermore, the synthesis of TE2A is rather simple and well-described in literature. 34 However, access to GluCAB-1 Mal was not simple, the secondary amine functions of the TE2A precursor (its tert-butyl diester derivative) being equivalent. A delicate statistical functionalization of these latter amines with the targeting groups was required leading to difficult purifications and poor yields.…”
Section: Introductionmentioning
confidence: 99%